2021
DOI: 10.1155/2021/4896106
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] DNM1: A Prognostic Biomarker Associated with Immune Infiltration in Colon Cancer—A Study Based on TCGA Database

Abstract: Aim. The aim of our work was to determine the utility of DNM1 as a biomarker for the diagnosis and prognosis of colon cancer (CC). Methods. DNM1 expression variations in CC vs. normal tissues were investigated using The Cancer Genome Atlas (TCGA) database. The association of DNM1 expression levels with the clinicopathological variables in CC prognosis was investigated using logistic regression analyses. Independent prognostic factors for CC were evaluated using univariate and multivariate Cox regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…8A), we found that the cell adhesion molecule GA733-2 antigen (GA733) can exist in the solution and dissociated colon cancer cells as a higha nity noncovalent cis dimer [24]. DNM1 can be used as a biomarker for the diagnosis and prognosis of CC, and it has also been proved that DNM1 was related to several cancer-related pathways, such as ECM receptor interaction and dilated cardiomyopathy [25]. For the top pathway in which low-risk groups participate (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…8A), we found that the cell adhesion molecule GA733-2 antigen (GA733) can exist in the solution and dissociated colon cancer cells as a higha nity noncovalent cis dimer [24]. DNM1 can be used as a biomarker for the diagnosis and prognosis of CC, and it has also been proved that DNM1 was related to several cancer-related pathways, such as ECM receptor interaction and dilated cardiomyopathy [25]. For the top pathway in which low-risk groups participate (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The low expression of DNM3 was significantly associated with high pathological grading of cervical cancer [ 71 ]. In contrast, DNM1 is overexpressed in H295R-PM-Ptc+ cells, as in colon cancer where high DNM1 expression was significantly correlated with perineural and lymphatic invasion and predicted poor prognosis [ 72 ]. Moreover, the overexpression of Huntingtin-interacting protein 1 ( HIP1 ) has also been observed in prostate and colon tumor cells where HIP1 expression was significantly associated with prostate cancer progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…This is the rst study elucidating the HFD-induced hepatic DNM1 over-expression might affect tumor development and immune microenvironment in human HCC. So far, the link between DNM1 and human cancer has only been observed at the mRNA level in the colon [10] and bladder [19] . None of the studies has indicated a possible role of DNM1 in the cancer promoting effects of high-fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the PH Domain of DNM1 are associated with a nonepileptic phenotype characterized by developmental delay and neurobehavioral abnormalities [8] . DNM1 has been implicated to be involved in the development of various tumors including, bladder cancer (BC) [9] , colon cancer [10] , non-small-cell lung cancer (NSCLC) [11] , and hepatocellular carcinoma (HCC) [12] ; yet, the underlying mechanisms by which DNM1 modulate tumorigenesis is unclear.…”
Section: Introductionmentioning
confidence: 99%